Phytochemical Constituents of Annona reticulata and their Cytotoxic Activity - Pham, Ty V.; Le, Thang Quoc; Le, Anh Tuan; Vo, Hung Quoc; Ho, Duc Viet (Letters in Organic Chemistry, 2020)
A phytochemical investigation of the leaves of Annona reticulata led to the isolation and structural determination of β-sitosterol (1), ent-pimara-8(14),15-dien-19-oic acid (2), ent-pimara- 8(14),15-dien-19-ol (3), quercetin (4), quercetin 3-O-α-L-arabinopyranoside (5), and a mixture of quercetin 3-O-β-D-galactopyranoside (6a) and quercetin 3-O-β-D-glucopyranoside (6b). Of these, compounds 2 and 3 were isolated from the genus Annona for the first time. Compound 3 showed strong cytotoxicity against SK-LU-1 and SW626 cell lines with IC50 values of 17.64 ± 1.07 and 19.79 ± 1.41 μg mL-1, respectively.
Keywords: SK-LU-1